THE RELATIONSHIP BETWEEN SUBSTANCE ABUSE AND VIOLENT BEHAVIOR IN PATIENTS WITH SCHIZOPHRENIA - Widiantoro, Fx. Wahyu; Pensiuna Wati, Finda (Widya Aksara : Jurnal Agama Hindu, 2025)
Substance abuse is often associated with violent behavior, particularly in patients with mental disorders such as schizophrenia. The combination of psychotic symptoms and the psychoactive effects of substances can worsen impulse control and increase the risk of aggressive actions. This study aims to analyze the relationship between substance abuse and violent behavior in patients with schizophrenia. This quantitative study employed a descriptive correlational design. The sample consisted of 100 respondents who met the inclusion criteria, selected using purposive sampling. Data were collected through questionnaires distributed online via social media. Data analysis was performed using simple linear regression tests with SPSS software. The findings revealed that substance abuse significantly affects violent behavior (p < 0.05). The regression coefficient of 0.947 indicates a positive relationship between the two variables. The R² value of 0.621 indicates that 62.1% of the variance in violent behavior can be explained by substance abuse, while the remaining 37.9% is influenced by other factors. This study found that substance abuse is a significant factor influencing violent behavior in patients with schizophrenia. Rehabilitation-based interventions for substance abuse and emotional regulation, such as Cognitive Behavioral Therapy (CBT), are essential to reduce the risk of violence in this population. This study provides empirical evidence for developing more holistic policies and intervention programs in managing patients with schizophrenia and substance abuse.